Monetary rewards modulate inhibitory control - Herrera, Paula M.; Speranza, Mario; Hampshire, Adam; Bekinschtein, Tristán A. (Frontiers in Human Neuroscience, 2014)
The ability to override a dominant response, often referred to as behavioural inhibiton, is considered a key element of executive cognition. Poor behavioural inhibition is a defining characteristic of several neurological and psychiatric populations. Recently, there has been increasing interest in the motivational dimension of behavioural inhibition, with some experiments incorporating emotional contingencies in classical inhibitory paradigms such as the Go/Nogo and Stop Signal Tasks. Several studies have reported a positive modulatory effect of reward on the performance of such tasks in pathological conditions such as substance abuse, pathological gambling, and ADHD. However, experiments that directly investigate the modulatory effects of reward magnitudes on the performance of inhibitory paradigms are rare and consequently, little is known about the finer grained relationship between motivation and self-control. Here, we probed the effect of reward and reward magnitude on behavioural inhibition using two modified version of the widely used Stop Signal Task. The first task compared no reward with reward, whilst the other compared two different reward magnitudes. The reward magnitude effect was confirmed by the second study, whereas it was less compelling in the first study, possibly due to the effect of having no reward in some conditions. In addition, our results showed a “kick start” effect over global performance measures. More specifically, there was a long lasting improvement in performance throughout the task, when participants received the highest reward magnitudes at the beginning of the protocol. These results demonstrate that individuals’ behavioural inhibition capacities are dynamic not static because they are modulated by the reward magnitude and initial reward history of the task at hand.